Paradigm shift in the resistance of grape isolates of Colletotrichum gloeosporioides to carbendazim and their biocontrol by Trichoderma harzianum - INDU S. SAWANT* and S.D. SAWANT, SHUBHANGI P. NARKAR, DINESH S. SHETTY (Indian Phytopathology, 2012)
In vitro sensitivity of a range of field isolates of Colletotrichum gloeosporioides to the benzimidazole fungicide, carbendazim, indicated a high level of resistance. All 27 isolates had carbendazim MIC values above 10 Î¼g/ml; four of these isolates were able to grow even at 1000 Î¼g/ml, indicating that all isolates were moderately to highly resistant to carbendazim. The highly resistant isolates were more virulent than the moderately virulent isolate and were able to produce symptoms in leaves treated with as high as 10000 Î¼g/ml carbendazim concentration. In vitro antagonism studies revealed that Trichoderma harzianum (NAIMCC-01965) could parasitize the highly resistant isolates as effectively as the moderately resistant isolate, while the four other Trichoderma spp. were less effective. Application of an aqueous suspension of T. harzianum (NAIMCC-01965) was as effective as 10000 Î¼g/ml carbendazim in suppressing development of symptoms in artificially inoculated Thompson Seedless leaves.